High throughput screening assay for the identification of ATF4 and TFEB activating compounds - Daniel J. Pfau; Ruslana Bryk (Autophagy Reports)
Macrophages act to defend against infection but can fail to completely prevent bacterial replication and dissemination in an immunocompetent host. Recent studies have shown that activation of a host transcription factor, TFEB, a regulator of lysosomal biogenesis, could restrict intramacrophage replication of the human pathogen Mycobacterium tuberculosis, and synergise with suboptimal levels of the antibiotic rifampin to reduce bacterial loads. Currently available small molecule TFEB activators lack selectivity and potency but could be potentially useful in a variety of pathological conditions with suboptimal lysosomal activity. TFEB nuclear translocation and activation depend on its phosphorylation status, which is controlled by multiple cellular pathways. We devised a whole cell, high throughput screening assay to identify small molecules that activate TFEB by establishing a stably transfected HEK293T reporter cell line for ATF4, a basic leucine zipper transcription factor induced by stress response and activated in parallel to TFEB. We optimised its use in vitro using compounds that target endoplasmic reticulum stress and intracellular calcium signalling. We report results from screening the commercially available LOPAC library and the Selleck Chemicals library modified to include only FDA-approved drugs and clinical research compounds. We identified 21 compounds across six clinical use categories that activate ATF4 and confirmed that two proteasome inhibitors promote TFEB activation. The results of this study provide an assay that could be used to screen for small molecules that activate ATF4 and TFEB and a potential list of compounds identified as activators of the ATF4 transcription factor in response to cellular stress.